Localization of fourier-laplace series of distributions - Ahmedov, Anvarjon; Nurullah, Ahmad Fadly; Rakhimov, Abdumalik (Institute for Mathematical Research, Universiti Putra Malaysia, 2013)
This work was intended as an attempt to extend the results on localization of Fourier-Laplace series to the spectral expansions of distributions on the unit sphere. It is shown that the spectral expansions of the distribution on the unit sphere can be represented in terms of decompostions of Laplace-Beltrami operator. It was of interest to establish sufficient conditions for localization of the spectral expansions of distribution to clarify the latter some relevant counter examples are indicated.